RANCANG BANGUN APLIKASI E-LEARNING MOBILE BERBASIS FLUTTER DI MA AL-ITTIHAD - Fasya, Nabiila; Aryono, Gagah Dwiki Putra; Auliana, Sigit (Politeknik Bisnis Indonesia, 2025)
The limitations of implementing digital learning methods at MA Al-Ittihad Pedaleman Tanara, particularly in the subject of Informatics, have resulted in low access to learning materials and interactions. This study aims to design and develop a mobile-based e-learning application using the Flutter framework to enhance the effectiveness, flexibility, and accessibility of the learning process. The development method used is the waterfall model, which consists of five stages: needs analysis, design, implementation, testing, and evaluation. The developed application provides key features such as digital learning materials, interactive practice questions, discussion forums, online evaluations, and task reminder notifications. Testing results show that the application runs well, supports interactive and flexible learning activities, and has received positive responses from students and teachers due to its ease of use and suitability to their needs. Thus, this application is expected to become an effective digital learning solution for madrasahs and contribute to promoting digital transformation in Islamic education, especially in areas that have not yet optimally utilized information technology.